A 12–27 GHz SiGe BiCMOS VGA with phase shift variation compensation. (December 2017) - Li, Zhenrong; Liu, Xintong; Zhuang, Yiqi
Abstract: This paper describes a 12–27 GHz VGA with low phase shift variation and dB-linear gain. A pre-distortion technique for extending the gain tuning range is employed to allow a dB-linear dynamic range of 31 dB, and a compensation structure for reducing the phase shift variation is adopted to make the phase shift varies less than 4° within the entire gain range. Besides, a DAC cell is innovatively introduced to achieve the dB linearity and low phase shift variation balance. A fourth-order LC-ladder filter is used for input matching and a peak inductor technique is used to broaden bandwidth of the VGA. The proposed variable gain amplifier operating in Ku and K bands is implemented in 0.18 μm BiCMOS technology. The simulation results show that the input and output return loss are less than −10 dB in the whole work frequency band, an IIP3 of −2.8 dBm, an IP1dB of −12 dBm and a power consumption of 62.1 mW are achieved at maximum gain mode in center frequency.